Femtosecond harmonic mode-locking of a fiber laser based on a bulk-structured Bi2Te3 topological insulator - Lee, Junsu; Koo, Joonhoi; Jhon, Young Min; Lee, Ju Han (OPTICAL SOC AMER, 2015)
We experimentally demonstrate femtosecond harmonic mode-locking of a fiber laser using a bulk-structured Bi2Te3 topological insulator (TI)-deposited on a side-polished fiber as a mode-locker. A bulk-structured Bi2Te3 TI film was prepared at a thickness of similar to 20 mu m using a mechanical exfoliation method. Using the mode-locker in an erbium-doped fiber ring cavity, it was experimentally shown that harmonically mode-locked pulses with temporal widths of 630 similar to 700 fs could readily be generated upto the 55th harmonics. The pulse repetition rate was shown to be tunable from the fundamental resonance frequency of 14.07 MHz to the harmonic frequency of 773.85 MHz with increasing pump power. The pumping efficiency was measured at similar to 3.36 MHz/mW. The side mode suppression ratio (SMSR) was observed to be more than 27.3 dB over all harmonic orders, while the corresponding signal-to-noise ratio (SNR) ranged from 46.3 to 63 dB. (C) 2015 Optical Society of America
Keywords: EVANESCENT FIELD INTERACTION; SATURABLE ABSORBER; CARBON NANOTUBE; GRAPHENE OXIDE; SOLITON LASER; ENERGY QUANTIZATION; PULSE GENERATION; BI2SE3